A new KD-3D-CA block cipher with dynamic S boxes based on 3D cellular automata - Hamdi, Ayman Majid (2019)
Due to the ubiquity of digital communications and digital data in today’s world, the development of techniques and tools to protect wireless communications and information transfer has become increasingly important. Currently, static substitution boxes (S-Boxes) are vulnerable to data and subkey attacks. Various techniques have been considered in the literature to improve S-Boxes using cellular automata (CA) with different rules such as 1-D, 2-D, and 3D CA rules. S-Boxes could either be static or dynamic. While the previous work provides some form of security, the latter work is better. A strong key expansion mechanism makes the cipher more resistant to various forms of attacks, especially related-key model attacks. Rijndael is the most common block cipher and it was adopted by the National Institute of Standards and Technology, USA in 2001 as an Advanced Encryption Standard (AES). However, cryptanalysts have revealed the security weaknesses of Rijndael in terms of its vulnerability to related-key differential and linear attacks that are mainly caused by lack of nonlinearity in its key schedule. Most research in the literature used fixed key expansion algorithm for encryption and decryption. However, the fixed key expansion is vulnerable to square attack. On the other hand, the round key expansion algorithms are relatively simple. Nevertheless, they may also be attacked easily. Considering the aforementioned challenges, this research proposes a new model for 3D-CA block cipher. First, potential problems in AES and CA block ciphers such as fixed key expansion, the static nature of S-Boxes, and the low level of data permutation for each round are identified and analyzed. The requirements of the intended KD-3D-CA block cipher and its rule for a key size of 128-bit are designed. After that, critical performance measurements and metrics used in 3D–CA are identified. The module of a KD-3DCA block cipher is designed and algorithms of the new KD-3D-CA block cipher are generated. KD-3D-CA cryptosystem security was tested using NIST statistical tools, Avalanche test, S-Box Evaluation Tool (SET) test, performance test, and complexity test. In this thesis, new algorithms are proposed for the key generation, encryption and decryption module of KD-3D-CA block cipher based on von Neumann (3D) cellular automata. The algorithms are tested for randomness and security by using the National Institute of Standards and Technology (NIST) statistical tests within nine datasets in the third and final rounds. Moreover, new dynamic S-Boxes are proposed and tested for their security characteristics using SET and CSET tools. Avalanche test is carried out for KD-3D-CA block cipher to ensure a single bit change in the key or plaintext forms different rounds. Half of the ciphertexts changed for each round. Eight 3D-CA-S-Boxes were also tested for their security characteristics with a particular focus on resistance to linear and differential attacks. The findings show that the proposed KD-3D-CA block cipher is more secure than the existing CA block ciphers. The KD-3D-CA block cipher was tested using nine different datasets with the following criteria: Avalanche key, Avalanche plaintext, CBC mode, correlation key and plaintext, low and high density for both plaintext and the key. Furthermore, this block cipher passed the NIST statistical test which satisfies the randomness criteria in different rounds with alpha values 0.01 and 0.001. The proposed 3D S-Boxes meet the security requirements of an efficient S-Box such as balance, completeness, Strict Avalanche Criterion (SAC), nonlinearity, bit independence, differential uniformity (DU), inevitability, and non-contradiction. The S-Boxes exhibit an equal performance when compared with the AES S-Box and they are resistant to attacks such as differential and linear attacks. Moreover, the block cipher passes the Avalanche Effect Test with a result of 0.01, which indicates a satisfactory key expansion property. Lastly, KD-3D-CA Block cipher is more complex and it outperforms AES with more than 25% for different key sizes. Deductively, the proposed KD-3D-CA block cipher algorithm is more secure than other block cipher algorithms and can be implemented for data encryption and decryption.